Kinetically controlled synthesis of cefaclor with immobilized penicillin acylase in the presence of organic cosolvents - Zhang, Ye-Wang (Array, 2008)
Summary: Enzymatic syntheses of cefaclor with immobilized penicillin acylase in organic cosolvents under kinetic control were carried out. KcPGA from Kluyvera citrophila was selected as the best catalyst among the three species of immobilized penicillin acylase. Ethylene glycol, glycerol, methanol, ethyl estate and polyethyleneglycol (PEG) were selected accordingly and cefaclor syntheses were preformed respectively. Best results in terms of yield were obtained in ethylene glycol, with which further studies were investigated and the maximum yield was Y = 93.5 %. The optimal conditions were pH 6.5, temperature θ = 5 °C, 3 mol D-phenylglycine methyl ester (PGME) per mol 7-aminodesacetoxymehtyl-3-chlorocephalosporin acid (7ACCA) and x = 30 % ethylene glycol fraction. Under above mentioned conditions, the yield was Y = 91.1 %